PERENCANAAN STRUKTUR BANGUNAN BAWAH JEMBATAN RANGKAS PANJANG KECAMATAN KRAGILAN KABUPATEN SERANG - Sihabudin Sihabudin; Bambang Hariyanto; M Ichwanul Yusup (Journal of Sustainable Civil Engineering (JOSCE), 2021)
Bridges are an easy solution to smooth the flow of traffic, but can cause more complex problems such as encouraging people to use more private cars and of course things like this can make more cars. In the end, non-toll roads will get an increase in the volume of traffic and can increase parking needs which are further increasing.Primary data and secondary data from the results of information obtained directly or indirectly are presented in two kinds of forms, namely calculations and supporting images for planning the structure of the bridge under the bridgeThe results of the analysis of the Rangkas Panjang Lower Bridge Structure Planning, the results of the planning have been calculated the dimensions of the structure of the bridge base (abutment) which is determined based on the needs of the local geological structure and provisions, certain requirements are able to withstand burdens due to loading and forces that occur at the base of the bridge ( abutment) that is, with a safety factor (SF) = 17.74> 1.5 and against a sliding Safety Factor (SF) = 2.79> 1.5. The foundation is used wells foundation with a diameter of 3.00 m totaling two pieces on the abutment